Substansi dan Relevansi Nafkah Keluarga Dalam Perundang-Undangan Hukum Keluarga Islam : Analisis Struktural Fungsional - Oktalita, Frina; Avita, Nur (ASASI: Journal of Islamic Family Law, 2023)
This paper aims to strengthen the opinion and concept of living in various contemporary Islamic family laws. This paper is a qualitative research of several sources of data from laws, books and literary works that discuss livelihoods and describe the role of the wife as breadwinner by means of analysis using structural functional theory by a Sociological approach. The results of this study reveal that the wife as the breadwinner is relevant to current conditions when analyzed by structural functional theory, that in a family it is expected that there is a husband or wife who can ensure the survival of the household. So that what is needed in the household is an attitude of mutual understanding between husband and wife, if this goal is achieved then conflicts and problems in the family can be avoided